PENGARUH BOBOT POTONG DAN PAKAN KOMERSIAL TERHADAP PERTUMBUHAN AYAM BROILER - Muhammad Sawadi; Harapin Hafid; La Ode Nafiu (Universitas Halu Oleo, 2016)
This study aims to examine the different weighting and different types of commercial feeds on the growth of broiler chickens. The study was prepared based on Completely Randomized Design (RAL) of 4 x 3 and 3 replication factorial patterns. The first factor is Grouping Cut Off (600 - 1000 grams or ± 800 g, 1,100 - 1300 g or ± 1,200 grams, 1,400-1,700 or ± 1,600 grams, 1,800 - 2200 g or ± 2,000). The second factor is the type of commercial feed / ration from different factories (AB1, BP11 and P11). Parameters measured include: feed intake, drinking water consumption, body weight gain, feed conversion and final cutting weight. The results of this study indicate that the use of commercial BP-11 feed on various commercial broiler feed factors resulted in increased body weight, better feed conversion compared with AB-1 and P-1 feed types. While the cut weight factor significantly affect the consumption of feed as weight gain and cut weight. At the cut weight of 1100-1500 grams, the average feed conversion produced is the lowest that is 1.26 which indicates that this cut weight is most favorable with the smallest feed efficiency. Keywords: cutting weight, commercial feed, growth, feed consumption, average daily gain, feed conversion, broiler chicken